Association between waist-to-height ratio and osteoporosis in the National Health and Nutrition Examination Survey: a cross-sectional study - Li, Hailong; Qiu, Jianfeng; Gao, Zhe; Li, Chun; Chu, Jianjun (Frontiers in Medicine, 2024)
BackgroundThe link between waist-to-height ratio (WHtR) and osteoporosis (OP) remains a contentious issue in the field of medical research. Currently, the available evidence on this association is deemed insufficient. This topic has garnered significant attention and is a focal point of ongoing investigations.MethodsA retrospective cross-sectional study was conducted, involving 5,746 participants from the National Health and Nutrition Examination Survey. Data on various demographic and clinical parameters, including age, gender, race, poverty income ratio, educational level, smoking status, drinking status, cardiovascular disease, hypertension, diabetes mellitus, hemoglobin A1c, alanine transaminase, aspartate transaminase, serum total bilirubin, serum creatinine, uric acid, blood urea nitrogen, serum sodium, serum phosphorus, total calcium, serum potassium, and serum iron, were collected from all participants. The main analytical methods utilized in this study were multivariable logistic regression, restricted cubic splines, and threshold effect analysis to investigate the association between WHtR and OP.ResultsA total of 5,746 elderly participants were enrolled, with a median age of 69.3 years. Compared with individuals with lower WHtR Q1 (≤0.36 to ≤0.56), the adjusted OR values for WHtR and OP in Q2 (<0.56 to ≤0.61), Q3 (<0.61 to ≤0.66), and Q4 (<0.66 to ≤ 0.94) were 0.63 (95% CI: 0.47–0.85, p = 0.003), 0.53 (95% CI: 0.37–0.76, p < 0.001), and 0.49 (95% CI: 0.35–0.68, p < 0.001), respectively. The association between WHtR and OP exhibited an L-shaped curve (nonlinear, p = 0.008) with an inflection point of roughly 0.57. The OR for the presence of OP was 0.50 (95% CI: 0.31–0.82, p = 0.007) in participants with WHtR <0.57. There was no association between WHtR and OP in participants with WHtR ≥0.57.ConclusionThe association between WHtR and OP showed an L-shaped curve, with an inflection point at around 0.57.